Examining the relationship between work ergonomic and task performance: a study at SSM Negeri Sembilan / Aina Shareena Shaidi - Shaidi, Aina Shareena (Faculty of Business and Management, 2020)
The research objective is to examine whether work ergonomic include physical ergonomic and organizational ergonomic have a positive relationship on task performance. The target respondents in this study are employees who work at Suruhanjaya Syarikat Malaysia (SSM) Negeri Sembilan from different department consists of Operation, Enforcement and Corporate with a total population of 35 employees. A sample size consists of 32 employees have been chosen to complete the questionnaires. Simple random sampling has been used as sampling technique for the study. The researchers used questionnaire as the tool to collect data for this study. Data has been analyzed through Statistical Package for Social Sciences (SPSS). Frequency analysis, Descriptive statistics, Correlation and Multiple Regression analysis has been applied to explain the results of the study. This is mainly to answer the research objectives. The findings of the study shown that there is a positive relationship between physical ergonomic and task performance which prove H1 hypothesis is accepted. The result for organizational ergonomic indicates there is insignificant relationship between organizational ergonomic and task performance which prove H2 hypothesis is rejected. The result of this study will be useful to the organization and employee to have deeper understanding how work ergonomic influenced on task performance. It allowed the organization to be able to implement policy, remuneration or plan to retain their work systems.